On the Interdependence Between Contents and Literary Forms in Parmenides’ Poem - Costa, Alexandre (Revista Archai, 2024)
Starting from the identification and characterization of three literary forms that coexist throughout Parmenides’ Poem, all of them plainly different from each other, it is proposed and demonstrated that such a variety of forms mirrors the delimitation of the different ways of thought and language elaborated by Parmenidic philosophy, in which at least two types of nature of knowledge must be recognized: the logical and the cosmological. The first, marked by a formally logical-argumentative speech which is given the name of truth (aletheia) and whose way of thinking is exclusively noetic; the second, of a theoretical-descriptive nature, dedicated to the consideration of the movement proper to cosmic phenomena, whose devenir demands an equally mobile way of thinking (phronein).